Predicting Coping With Self-Regulated Distance Learning in Times of COVID-19: Evidence From a Longitudinal Study - Berger, Fred; Schreiner, Claudia; Hagleitner, Wolfgang; Jesacher-Rößler, Livia; Roßnagl, Susanne; Kraler, Christian (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, students worldwide have experienced fundamental changes to their learning. Schools had to shift to distance education as part of the effort to stop the spread of the virus. Although distance learning undoubtedly resulted in challenges for all students, there is much concern that it exacerbated existing educational inequalities and led to disadvantages – particularly for students who were already struggling academically and lacking support from family and school. The aim of this paper was to investigate the possible impact of family and child characteristics, school performance prior to lockdown, and support at home and from school during lockdown in coping with self-regulated distance learning during times of COVID-19. The paper draws on data from a two-wave longitudinal study surveying 155 lower secondary school students aged 13–14years from a rural-alpine region in Austria. Data were collected 1year before the start of the pandemic and directly after schools had returned to in-class teaching after the first lockdown. Our findings support the notion that distance learning poses a substantial risk for exacerbating existing educational disadvantages. They show that coping with out-of-school learning was especially challenging for students with low academic achievement and learning motivation prior to the pandemic. Furthermore, findings demonstrate that the support from parents and teachers foster students’ capabilities to cope with the self-regulatory demands connected with distance learning. Although the importance of competencies for self-regulated learning became particularly evident in the context of the pandemic, from our findings, it can be concluded that in the future, schools should strengthen their investment in promoting competencies for self-regulated learning. Self-regulation must be recognized as an essential educational skill for academic achievement and life-long learning.